2000
DOI: 10.1103/physreve.61.2232
|View full text |Cite
|
Sign up to set email alerts
|

Tricritical points in the Sherrington-Kirkpatrick model in the presence of discrete random fields

Abstract: The infinite-range-interaction Ising spin glass is considered in the presence of an external random magnetic field following a trimodal (three-peak) distribution. Such a distribution corresponds to a bimodal added to a probability p 0 for a field dilution, in such a way that at each site the field h i obeys

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…For continuous transitions, For the particular case σ = 0, i.e., the bimodal probability distribution for the fields [25], (1) 0 (σ) as a collapse of two tricritical points. Such an unusual critical point is a characteristic of some infinite-range-interaction spin-glasses in the presence of random magnetic fields [25,26], and to our knowledge, it has never been found in other magnetic models. ¿From (1) 0 (σ)/σ decreases.…”
Section: Standart Calculations Lead Tomentioning
confidence: 72%
See 2 more Smart Citations
“…For continuous transitions, For the particular case σ = 0, i.e., the bimodal probability distribution for the fields [25], (1) 0 (σ) as a collapse of two tricritical points. Such an unusual critical point is a characteristic of some infinite-range-interaction spin-glasses in the presence of random magnetic fields [25,26], and to our knowledge, it has never been found in other magnetic models. ¿From (1) 0 (σ)/σ decreases.…”
Section: Standart Calculations Lead Tomentioning
confidence: 72%
“…The model is considered in the limit of infinite-range interactions, and the probability distribution for the random magnetic fields is a double Gaussian, which consists of a sum of two independent Gaussian distributions. Such a distribution interpolates between the bimodal and the simple Gaus-sian distributions, which are known to present distinct low-temperature critical behavior, within the mean-field limit [24,25,26,27]. It is argued that this distribution is more appropriate for a theoretical description of diluted antiferromagnets than the bimodal and Gaussian distributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible consequence of the transverse field, induced longitudinal RF, is that the Almeida-Thouless (AT) line 22 can be sup-pressed, as suggested by numerical simulations in shortrange-interaction SGs 23 . However, previous studies using mean-field Parisi's framework have shown that the SK model with a RF does preserve the AT line [24][25][26][27][28] . Consequently, assuming that Parisi's mean-field theory is a valid framework to describe the SG problem with a transverse field, induced longitudinal RF, one can also raise the question of how the behavior of χ 3 can be related with the AT line, when a RF is present in the SK model?…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies display broad divergences even for the RFIM phase diagram structure [4,[7][8][9]. On the other hand, the effect of RFs on the SG phase has also been investigated [10][11][12][13][14]. In this case, random bond (RB) interaction models with an additional magnetic RF have been considered extensively.…”
Section: Introductionmentioning
confidence: 99%